PERBEDAAN AKTIVITAS ANTIOKSIDAN PADA KOLANG KALING SEGAR DAN KOLANG KALING SERBUK - Eka Susanti Hanhadyanaputri; Ariani Hesti Wulan; Indah Sulistyarin; Intan Martha Cahyani (Jurnal Insan Farmasi Indonesia, 2023)
Kolang kaling (Arenga pinnata) is one of the results of the palm tree. The process of processing palm fruit into and fro can affect the quality of the fruit and fro produced.  The purpose of this study was to determine the physico-chemical characteristic, IC 50 value of fresh fruit and fro, the powder was dried in the microwave at low temperature (40oC) for 5 days, medium (53oC) for 4 hours and high (78oC) for 2 hours, and to find out whether there are effect of difference in fresh fruit and fro treatment on antioxidant activity.  Fresh fruit and fro were tested for phytochemical screening and FTIR, physicochemical characteristics and antioxidant, Antioxidant testing used the DPPH (1,1-diphenyl-2-picrylhidrazyl) method. The results of phytochemical screening and FTIR showed the presence of galactomanan compounds.  The antioxidant test results obtained the IC50 value of fresh fruit and fro, the powder was dried in the microwave at low temperature, medium and high respectively 104.8488; 25.2963; 90.0155 and163.4381 ppm. The statistical test results showed a value of 0.000<0.05,  there is a difference IC50 between groups